Mainstreaming Gender into Extractive Industries Projects : Guidance Note for Task Team Leaders - Eftimie, Adriana; Heller, Katherine; Strongman, John (World Bank, Washington, DC, 2014)
Extractive industries (EI) can bring many positive development impacts to the communities involved, but also have the potential to create or exacerbate vulnerabilities within these communities. Benefits and risks are often evaluated and measured at the community level, with little examination of the different impacts on men and women. In fact, evidence suggests that a gender bias exists in the distribution of risks and benefits in EI projects: benefits accrue to men in the form of employment and compensation, while the costs, such as family and social disruption, and environmental degradation, fall most heavily on women. Despite the ample evidence of gender bias, and its implications, in EI, there is significant scope for increasing the gender focus of most EI projects in the World Bank. Analyzing and adapting projects to local gender issues can help to mitigate the risks created by EI, and amplify the potential benefits to both men and women, leading to increased profitability and more sustainable development impacts. Furthermore, understanding and adapting projects to improve gender sensitivity is essential to realizing the Bank's stated commitment to both mainstreaming gender and to the third Millennium Development Goal (MDG) of gender equality and empowerment of women. The following guidelines briefly outline some of the ways that EI can impact men and women differently and the associated development implications, and provide step by step suggestions for how to understand and integrate gender issues into World Bank Group EI project design.